Effect of the Base of the Shoe Heel on Postural Stability During Walking in Women - FALOLA, JEAN-MARIE; Koussihouèdé, Fifamè Eudia Nadège; Falola, Stève Marjelin Donan; AVOSSEVOU, GABRIEL YVES HUGUES; Bio Nigan, Issiako; DANSOU, HOUNDJOVI PIERRE (My University, 2015)
The high-heeled shoes are the cause of slips and falls while walking. Objective: To determine the shape of the base of the heel of the shoe to a stabilization of the locomotor pattern of walking. Materials and Methods: Fifteen young women had normal-weighted market shoes without heel and with heels of 5.08 cm; 7.6 cm and 10 cm. Each shoe were associated three square bases whose sides were: small: 1.5 cm; average: 3 cm wide and 5.3 cm. Results: Significant differences between the kinematic parameters were only for small and medium bases. There was no significant difference between the large base and the heel without shoes. The base of the heel of the shoe that stabilizes the locomotor pattern of walking is one that is large and whose side is equal to 5.3 cm. This value represents the heel of the foot width of the subject
Keywords: Gait; Kinematic Parameters; High Heels; Base of the Heel